UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS IV SD NEGERI 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Deden Kusdinar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Based on the author’s teaching experience at SD Negeri 010 Banjar Panjang Kerumutan, as well as observations and preliminary reflections, it was found that students’ creativity in learning was still low, which ultimately resulted in low learning outcomes, particularly in Natural Sciences. This condition was evident from the mid-semester test results, which showed that classical mastery reached only 50%, or 10 out of 20 students. The minimum mastery criterion (KKM) for Natural Sciences in Grade IV at SD Negeri 010 Banjar Panjang Kerumutan was set at 70. The low learning outcomes were caused by several factors related to teaching practices, including the frequent use of lecture-based methods, the assumption that students’ learning abilities were equal, and a learning process that was predominantly teacher-centered. This study employed Classroom Action Research (CAR), conducted through the stages of planning, implementation, observation, and reflection. The research findings indicate a significant improvement in students’ science learning outcomes from the preliminary data to Cycle I and Cycle II. Initially, only 50% of students achieved mastery. This increased to 70% in Cycle I and further improved to 85% classical mastery in Cycle II.